The Sorption Studies of Waste Cooking Oil using Raw and Treated Pineapple Crown Leaf - Rabuyah, Ni; Abdul Somad, Mustapha Kama; Shahrina, Shah Jahan; Siti Hajijah, Ismail; Harunal Rejan, Ramji (UiTM Press, Universiti Teknologi MARA, 2024)
The unregulated discharge of pollutants into water bodies has become an issue that led to pollution. Fiber derived from various forms of agricultural wastes as the sorbent is widely used as it has a high sorption capacity and efficiency. It is environmentally friendly and could be costeffective as it only utilizes the unwanted parts of plants, which usually would otherwise be discarded. The pineapple crown leaf (PCL) and other plants with high cellulose content have the potential for environmental applications. Oil pollutants, particularly waste cooking oil (WCO) from the food and beverage industry, often contaminate water bodies due to poor waste management. Using cellulose-rich plants like PCL could offer an effective solution for absorbing these pollutants. This study examines the characteristics and sorption capacities of raw, NaOH-treatment PCL, and carbonized PCL to develop an effective, eco-friendly method for oil spill remediation. The methodology involves washing, drying, grinding, and sieving PCL to obtain a powdered PCL. Then, raw PCL (RPCL) undergoes chemical treatment with 10% sodium hydroxide, NaOH and thermal treatment at 300 °C. The raw and treated PCL were characterized using Fourier Transform Infrared Spectroscopy (FTIR). The elimination of some noncellulosic components in NaOH-treatment PCL (CPCL) and carbonized PCL (TPCL) observed in the FTIR spectrum would contribute to higher sorption efficiency and capacity of WCO. In agreement with the results from FTIR analysis, the highest sorption efficiency in pure oil was shown by TPCL at 33% and CPCL in slick oil at 16.33%. The highest value for pure and slick oil recorded for sorption capacity was 9.23 g g −1 from TPCL samples and 4.3 g g −1 from CPCL samples. This study supports sustainable waste management and green technology for environmental remediation, highlighting PCL's potential in mitigating oil pollution and the value of agricultural waste in creating eco-friendly solutions for oil disposal challenges.